Recycled carbon fiber reinforced nylon 6 composite and method of making the same

CN122978696APending Publication Date: 2026-10-27SUZHOU SUNWAY POLYMER
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611412951.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-11
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0004]鉴于以上所述现有技术的缺点,本发明的目的在于提供一种回收碳纤维增强尼龙6复合材料及其制备方法,用于解决现有技术中含尼龙6残胶的回收碳纤维难以被有效活化、强氧化除胶处理易造成碳纤维表面缺陷和强度损失、再次熔融加工时碳纤维与尼龙6基体界面结合不足以及纤维过度断裂导致再生材料力学性能和耐热性能下降的问题

Benefits of technology

1、本发明先选择性去除老化尼龙6残胶、再进行氧等离子体活化的处理顺序,使表面含氧官能团直接形成在回收碳纤维本体上,避免了官能团随残胶后续去除而损失;相比之下,现有技术在未先除残胶的情况下直接进行活化或偶联处理,处理剂主要作用于残胶层而难以稳定到达碳纤维本体,界面改性效果受到根本性限制。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application provides a recycled carbon fiber reinforced nylon 6 composite material and a preparation method thereof, and the material comprises nylon 6 resin, surface-reconstructed recycled carbon fiber, nylon 6 compatible compatibilizer containing anhydride groups, an antioxidant and a dispersing agent; the surface-reconstructed recycled carbon fiber comprises a recycled carbon fiber body and a silane interface layer containing exposed amino groups loaded on the surface of the recycled carbon fiber body; the recycled carbon fiber body is derived from waste carbon fiber reinforced nylon 6 material, the surface residual glue content of the recycled carbon fiber body is not higher than 1.5 wt%, and the surface oxygen-carbon atomic ratio is 0.15-0.25; and the dry matter mass of the silane interface layer is 0.5%-1.5% of the mass of the recycled carbon fiber body. The application can directly establish a chemical bonding type continuous interface on the recycled carbon fiber body, the silane interface layer containing exposed amino groups and PA6-g-MAH form a reaction bridge in a melting process, and the mechanical properties and heat resistance of the regenerated composite material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of recycled polymer composite materials technology, and in particular to a recycled carbon fiber reinforced nylon 6 composite material and its preparation method. Background Technology

[0002] Carbon fiber reinforced nylon 6 composites are widely used in the automotive, electronics, and machinery industries due to their high specific strength, specific modulus, and processability. With the increasing quantity of such products and production scraps, the recycling and reuse of carbon fibers in waste carbon fiber reinforced nylon 6 materials is of great significance. After being crushed, the carbon fiber surface of waste materials is usually covered with aged nylon 6 residues that have undergone multiple thermal histories. These residues can obscure effective bonding sites on the carbon fiber surface and further degrade under thermo-oxidative conditions during reprocessing. The recycling process also damages the original sizing layer, resulting in insufficient polar functional groups on the carbon fiber surface. This leads to insufficient interfacial bonding between the carbon fiber and the matrix in the recycled composite material, carbon fiber agglomeration, and excessive breakage, causing a decline in the mechanical and heat resistance properties of the recycled material.

[0003] Chinese patent CN 102181150A discloses a method for treating waste carbon fiber with epoxy resin or concentrated nitric acid and a silane coupling agent, followed by melt blending with nylon 6. Chinese patent CN 103554904A discloses a method for surface-treating recycled carbon fiber with silane, titanate, or aluminate before blending with nylon. However, the activation or coupling treatments in these methods do not first remove the aged nylon 6 residue from the carbon fiber surface; the treatment agent mainly acts on the residue layer and is difficult to stably reach the carbon fiber body. If high-temperature calcination or strong oxidation treatment is used to simultaneously remove the adhesive and activate the fiber, it easily causes surface defects and strength loss in the carbon fiber. Summary of the Invention

[0004] In view of the shortcomings of the prior art described above, the purpose of this invention is to provide a recycled carbon fiber reinforced nylon 6 composite material and its preparation method, which solves the problems in the prior art where recycled carbon fibers containing nylon 6 residue are difficult to effectively activate, strong oxidation degumming treatment easily causes carbon fiber surface defects and strength loss, insufficient bonding between carbon fiber and nylon 6 matrix interface during remelting and processing, and excessive fiber breakage leading to a decrease in the mechanical properties and heat resistance of recycled materials.

[0005] To achieve the above and other related objectives, the present invention provides the following technical solutions: In a first aspect, the present invention provides a recycled carbon fiber reinforced nylon 6 composite material, comprising nylon 6 resin, surface-reconstructed recycled carbon fiber, a nylon 6 compatibilizer containing anhydride groups, an antioxidant, and a dispersant. The surface-reconstructed recycled carbon fiber includes a recycled carbon fiber body and a silane interface layer containing exposed amino groups loaded on the surface of the recycled carbon fiber body; the recycled carbon fiber body is derived from waste carbon fiber reinforced nylon 6 material, and its surface residual adhesive content is not higher than 1.5 wt%, and the surface oxygen-carbon atom ratio is 0.15 to 0.25; the dry matter mass of the silane interface layer is 0.5% to 1.5% of the mass of the recycled carbon fiber body.

[0006] Among them, the silane interface layer containing exposed amino groups on the surface of the reconstructed carbon fiber can undergo a ring-opening reaction with the anhydride groups in the nylon 6 compatibilizer containing anhydride groups during the melt blending process. At the same time, the nylon 6 segments in the compatibilizer are compatiblely entangled with the matrix nylon 6, thereby forming a chemically bonded continuous interface between the carbon fiber body and the nylon 6 matrix. Compared with the purely physical adsorption interface, it has higher load transfer capacity and heat and moisture resistance.

[0007] Further, the content of the nylon 6 resin is 65-80 parts, the content of the surface-reconstructed recycled carbon fiber is 15-30 parts by weight, the content of the nylon 6 compatibilizer containing anhydride groups is 3-6 parts by weight, the content of the antioxidant is 0.3-0.8 parts by weight, and the content of the dispersant is 0.2-0.4 parts by weight.

[0008] Furthermore, the anhydride-containing nylon 6 compatibilizer is maleic anhydride-grafted nylon 6 (PA6-g-MAH), with a maleic anhydride grafting rate of 0.6% to 1.2%. The maleic anhydride groups in maleic anhydride-grafted nylon 6 can undergo ring-opening reactions with the primary amino groups in the aminosilane layer on the carbon fiber surface to form chemical bonds. Its nylon 6 segments are compatible and entangled with the matrix molecular chains, improving interfacial bonding while having minimal impact on the material's rigidity and heat resistance.

[0009] Preferably, the relative viscosity of the nylon 6 resin is 2.3 to 2.7. If the relative viscosity is too low, the matrix molecular chains will not be sufficiently entangled; if it is too high, it will increase the difficulty of dispersing recycled carbon fibers and increase extrusion shear.

[0010] Furthermore, the antioxidant is composed of hindered phenolic antioxidants and phosphite antioxidants, with a mass ratio of hindered phenolic antioxidants to phosphite antioxidants of 1:1 to 1:3. The hindered phenolic antioxidants provide primary antioxidant function, while the phosphite antioxidants provide secondary antioxidant function. The combination of the two can effectively inhibit the thermo-oxidative degradation of nylon 6 during high-temperature processing.

[0011] Furthermore, the dispersant is one or both of ethylene bis-stearamide and montanate, used to reduce friction between recycled carbon fiber bundles and improve side-feeding stability. An appropriate amount of dispersant is beneficial to reduce the agglomeration of high-content recycled carbon fibers.

[0012] As a preferred embodiment, the composite material further includes nylon 6 carrier carbon black masterbatch, with a content of 0 to 1 part by weight, to meet the coloring or electrostatic conductivity requirements of the product.

[0013] A second aspect of the present invention provides a method for preparing surface-reconstructed recycled carbon fibers, comprising the following steps: (1) The recycled carbon fiber containing nylon 6 residue was graded and pre-dried; (2) The pre-dried recycled carbon fiber obtained in step (1) is added to an aqueous formic acid solution with a mass concentration of 80% to 90% and subjected to low-shear extraction at 50 to 70°C to selectively dissolve the nylon 6 residue. After graded displacement washing and vacuum drying, the residue content is reduced to no more than 1.5% by mass. (3) Place the degummed recycled carbon fiber obtained in step (2) into a plasma treatment chamber with a turning mechanism, introduce oxygen-containing gas, and perform low-temperature oxygen plasma activation treatment. Control the carbon fiber temperature to be no higher than 80°C so that the surface oxygen-carbon atom ratio of the obtained recycled carbon fiber body reaches 0.15 to 0.25, and the carbon fiber tensile strength retention rate is no less than 90%. (4) Within 0.5 to 2 hours after the oxygen plasma activation in step (3), the pre-hydrolyzed aminosilane is applied to the surface of the recycled carbon fiber body obtained in step (3), so that the dry matter loading of the aminosilane is 0.5% to 1.5% of the mass of the recycled carbon fiber body. Then, after drying and heat treatment, a silane interface layer containing exposed amino groups is formed to obtain the surface reconstructed recycled carbon fiber.

[0014] The above preparation method involves selectively dissolving and removing residual nylon 6 adhesive, then activating the exposed carbon fibers with oxygen plasma, and finally loading an aminosilane interface layer. This sequence avoids the loss of oxygen-containing functional groups or the interface layer formed earlier due to the subsequent removal of residual adhesive, ensuring that the interface layer is directly established on the carbon fiber body.

[0015] Furthermore, in step (1), after pre-drying, the moisture content of the recycled carbon fiber is not higher than 0.3 wt%.

[0016] Furthermore, in step (2), the extraction temperature is 55–65°C, the extraction time is 40–60 min, and the liquid-to-solid ratio is 10–12 mL / g. Within this preferred parameter range, the optimal balance is achieved between the dissolution efficiency of formic acid on nylon 6 residue and the protection of the carbon fiber body.

[0017] Further, in step (2), the washing process includes: rinsing with an aqueous formic acid solution of the same concentration as the extract, followed by washing 2-3 times with a mixture of ethanol and water at a volume ratio of 70:30 to 90:10, and finally washing with deionized water until the pH of the washing solution is 6.0-7.0 and the conductivity is not higher than 100 μS / cm; the vacuum drying conditions are 80-100℃, vacuum degree not higher than -0.08 MPa, and drying for 3-6 hours. This graded replacement washing method can gradually reduce the concentration of formic acid and dissolved nylon 6 in the fiber gaps, effectively reducing residues.

[0018] Further, in step (3), the oxygen-containing gas is oxygen or an oxygen-argon mixture with an oxygen volume fraction of not less than 60%; the plasma activation treatment conditions are: gas pressure 20-80 Pa, power 100-250 W, treatment time 3-8 min, and agitation speed 5-20 r / min. By limiting the power, time, and fiber temperature, the plasma only slightly etches and oxidizes the surface of the carbon fiber, introducing oxygen-containing functional groups such as hydroxyl, carbonyl, and carboxyl groups, while controlling the tensile strength retention rate of the carbon fiber to not less than 90%.

[0019] Further, in step (4), the aminosilane is selected from alkoxysilanes containing primary amino groups, and the alkoxysilane containing primary amino groups is selected from γ-aminopropyltriethoxysilane. The silanol group generated after hydrolysis of γ-aminopropyltriethoxysilane can condense with the oxygen-containing functional groups on the carbon fiber surface to form a stable covalently bonded interface layer, and the aminopropyl group provides a primary amino group that can react with maleic anhydride groups to the outside.

[0020] Preferably, the preparation conditions of the alkoxysilane treatment solution containing primary amino groups are as follows: the mass concentration of the alkoxysilane containing primary amino groups is 0.5%–1.5%, the volume ratio of ethanol to water is 70:30–90:10, the pH is adjusted to 4.5–5.5 with acetic acid, and pre-hydrolyzes at 20–30°C for 20–40 min; the application method is impregnation, spraying, or atomization. Pre-hydrolyzing ensures that the alkoxy groups are fully converted into silanol groups, which is beneficial for subsequent condensation reactions with oxygen-containing functional groups on the carbon fiber surface.

[0021] Further, in step (4), the drying conditions are 70-90℃ for 1-2 hours, and the heat treatment conditions are 105-120℃ for 30-60 minutes. The heat treatment causes sufficient condensation between silanol groups and between silanol groups and oxygen-containing functional groups on the carbon fiber surface, forming a stable silane interface layer with exposed amino groups.

[0022] A third aspect of the present invention provides a method for preparing recycled carbon fiber reinforced nylon 6 composite material, comprising the following steps: S1. Nylon 6 resin, nylon 6 compatibilizer containing anhydride groups, antioxidant and dispersant are mixed to obtain resin premix; S2. The resin premix is ​​fed into the co-rotating twin-screw extruder through the main feed port. After the nylon 6 resin has been plasticized, the surface reconstructed recycled carbon fiber prepared above is fed into the side feed port downstream of the melt zone. The temperature of the twin-screw extruder from the main feed port to the die head is controlled at 220-250°C and the screw speed is 250-400 r / min. S3. The extrudate obtained in step S2 is cooled, pelletized, and vacuum dried at 80-100°C for 3-6 hours to obtain the recycled carbon fiber reinforced nylon 6 composite material.

[0023] Preferably, the twin-screw extruder has a length-to-diameter ratio of 36 to 48 and a screw speed of 300 to 380 r / min.

[0024] In some embodiments, in step S2, no more than two sets of kneading elements are provided downstream of the side feed port, and a vacuum exhaust section with a vacuum degree of -0.06 to -0.09 MPa is provided. The limited number of kneading elements ensures the dispersion of carbon fibers while reducing excessive breakage, and the vacuum exhaust section is used to remove volatile components, improving the appearance of the product and production stability.

[0025] Specifically, in step S2, the temperature from the main feed inlet to the die head is controlled sequentially as follows: 220–230°C, 225–235°C, 230–240°C, 235–245°C, 235–245°C, and 230–240°C. This temperature distribution is beneficial for the full plasticization of nylon 6 in the initial stage, and for maintaining a suitable melt viscosity in the middle and later stages to achieve uniform dispersion of carbon fibers, while avoiding thermo-oxidative degradation caused by excessively high temperatures.

[0026] As described above, the recycled carbon fiber reinforced nylon 6 composite material and its preparation method of the present invention have the following beneficial effects: 1. The present invention selectively removes residual nylon 6 resin first, and then performs oxygen plasma activation, so that oxygen-containing functional groups on the surface are directly formed on the recycled carbon fiber body, avoiding the loss of functional groups as the residual resin is subsequently removed; in contrast, the prior art performs activation or coupling treatment directly without removing the residual resin first, and the treatment agent mainly acts on the residual resin layer and is difficult to stably reach the carbon fiber body, and the interface modification effect is fundamentally limited.

[0027] 2. This invention uses an 80%–90% formic acid aqueous solution at 50–70°C for low-temperature, low-shear extraction. Formic acid has a selective dissolving effect on nylon 6 residue, and the temperature used is lower than the temperature at which carbon fibers suffer significant oxidative damage. The tensile strength retention rate of carbon fibers is not less than 90%. In contrast, the existing technology uses high-temperature calcination or strong oxidation treatment to remove adhesive and activate simultaneously, which easily leads to an increase in carbon fiber surface defects and strength loss, reducing the reinforcing effect of the composite material.

[0028] 3. This invention achieves chemical bonding bridging during the melting process of a silane interface layer containing exposed amino groups and a nylon 6 compatibilizer containing anhydride groups. The exposed amino groups on the carbon fiber surface undergo a ring-opening reaction with the maleic anhydride groups in the compatibilizer, while the nylon 6 segments of the compatibilizer simultaneously become entangled with the matrix nylon 6, forming a continuous chemically bonded interface of "carbon fiber body - oxygen-containing functional groups - aminosilane layer - compatibilizer - nylon 6 matrix". Compared with a purely physical adsorption interface, this interface exhibits higher interfacial bonding stability and load transfer capacity under high temperature and moisture absorption conditions, thereby improving the tensile strength, flexural strength, notched impact strength, and heat distortion temperature of the composite material.

[0029] 4. This invention uses a downstream side feeding method in the melting zone to introduce surface-reconstructed recycled carbon fibers into the plasticized nylon 6 melt. With no more than two sets of kneading elements and a vacuum exhaust section downstream of the side feed port, it can reduce excessive carbon fiber breakage and nylon 6 thermo-oxidative degradation, and improve the mechanical properties, heat resistance and production stability of the recycled material. Compared with the method of adding carbon fibers through the main feed port, this process makes the thermal history and shear history of the carbon fibers shorter, which is conducive to maintaining the effective reinforcement length of the carbon fibers. Detailed Implementation

[0030] The following specific embodiments illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. It should be noted that, unless otherwise specified, the following embodiments and features can be combined with each other. Unless otherwise specified, all parts of raw materials are parts by weight, and all solution concentrations are mass concentrations.

[0031] Raw materials and testing methods: In the following examples, the relative viscosity of the nylon 6 resin used was 2.5, and it was vacuum dried at 90°C for 4 hours before use.

[0032] The maleic anhydride grafting rate of maleic anhydride-grafted nylon 6 (PA6-g-MAH) is 0.8%, and it is vacuum dried at 80℃ for 3 hours before use.

[0033] The recycled carbon fiber containing residual adhesive is derived from waste long carbon fiber reinforced nylon 6 material, which is 3-8 mm in length after crushing and screening.

[0034] The aminosilane used is γ-aminopropyltriethoxysilane (KH550).

[0035] The antioxidants used are hindered phenolic antioxidant 1098 and phosphite antioxidant 168.

[0036] The dispersant used is ethylene bis-stearamide.

[0037] The color masterbatch uses nylon 6 carrier carbon black masterbatch.

[0038] Residual adhesive content determination: Thermogravimetric analysis was performed on dried recycled carbon fiber samples. The temperature was increased from room temperature to 700℃ under a nitrogen atmosphere. The residual adhesive content was calculated based on the mass loss in the main thermal decomposition range of Nylon 6 and after deducting the mass of the silane layer.

[0039] Surface oxygen-to-carbon atom ratio determination: The ratio of surface oxygen atom content to carbon atom content is determined using X-ray photoelectron spectroscopy. In the absence of X-ray photoelectron spectroscopy, recycled carbon fibers can be pressed into fiber felt and the water contact angle can be tested as a production process control indicator.

[0040] Mechanical property testing: tensile properties are tested according to ISO 527-2; flexural properties are tested according to ISO 178; notched impact strength is tested according to ISO 180; heat distortion temperature is tested according to ISO 75-2 Method B, 0.45 MPa load. At least 5 parallel specimens are tested in each group and the average value is taken.

[0041] The carbon fiber content of the composite material was tested using a segmented atmosphere method of thermogravimetric analysis: first, the nylon 6 matrix was thermally decomposed in a nitrogen atmosphere, and then the carbon fiber was oxidized by switching to an air atmosphere. The carbon fiber content was calculated based on the corresponding mass change.

[0042] Preparation Example 1 Preparation method of surface-reconstructed recycled carbon fiber A: (1) Take 1 kg of recycled carbon fiber containing residual nylon 6 and vacuum dry it at 90℃ for 3 h to make the moisture content not higher than 0.3 wt%; (2) The pre-dried recycled carbon fiber was added to 10L of an 85% formic acid aqueous solution with a liquid-to-solid ratio of 10mL / g, and subjected to low-shear extraction at 60℃ and 50r / min for 50min. Formic acid can selectively dissolve nylon 6 residue, and the temperature used is lower than the temperature at which the carbon fiber will suffer significant oxidative damage.

[0043] After extraction, hot filtration was performed at a temperature not lower than 40°C. The carbon fibers were then rinsed sequentially with 2L of 85% formic acid aqueous solution, followed by two washes with a 5L mixture of ethanol and water at a volume ratio of 80:20, and finally washed with deionized water until the pH of the washing solution reached 6.5 and the conductivity did not exceed 100 μS / cm. The washed carbon fibers were then vacuum-dried for 4 hours at 90°C and a vacuum degree not exceeding -0.08 MPa.

[0044] (3) Place the dried carbon fiber in a rotary low-temperature plasma treatment device, introduce oxygen, and treat it for 5 minutes under the conditions of oxygen pressure 40Pa, power 160W and turning speed 10r / min. Control the carbon fiber temperature not to exceed 80℃, so that oxygen-containing functional groups such as hydroxyl, carbonyl and carboxyl groups are introduced on the carbon fiber surface.

[0045] (5) Within 0.5 h after plasma treatment, prepare a KH550 ethanol-water treatment solution with a mass concentration of 1.0% and a volume ratio of ethanol to water of 80:20. Adjust the pH to 5.0 with acetic acid and pre-hydrolyze at 25 °C for 30 min. Spray the treatment solution onto the activated carbon fiber surface so that the KH550 dry matter loading is 1.0% of the carbon fiber mass.

[0046] Subsequently, it is dried at 80℃ for 1.5h, and then heat-treated at 115℃ for 45min to allow sufficient condensation between silanol groups and between silanol groups and oxygen-containing functional groups on the carbon fiber surface, forming a silane interface layer with exposed amino groups, thus obtaining surface-reconstructed recycled carbon fiber A.

[0047] The nylon 6 residual adhesive content of the surface-reconstructed recycled carbon fiber A was measured to be 0.7% by mass, the surface oxygen-carbon atom ratio was 0.19, and the carbon fiber tensile strength retention rate was 93%.

[0048] Preparation Example 2 Except for adjusting the formic acid concentration to 82%, immersing at 55°C for 60 min, adjusting the oxygen plasma treatment conditions to 30 Pa, 140 W and 6 min, and setting the KH550 dry matter loading to 0.8% of the mass of the recovered carbon fiber, the remaining operations were the same as in Preparation Example 1, and surface-reconstructed recovered carbon fiber B was obtained.

[0049] The nylon 6 residual adhesive content of the surface-reconstructed recycled carbon fiber B was measured to be 0.9% by mass, the surface oxygen-carbon atom ratio was 0.16, and the carbon fiber tensile strength retention rate was 95%.

[0050] Preparation Example 3 Except for adjusting the formic acid concentration to 88%, soaking at 65°C for 40 min, adjusting the oxygen plasma treatment conditions to 50 Pa, 180 W and 4 min, and making the KH550 dry matter loading 1.5% of the mass of the recycled carbon fiber, the other operations were the same as in Preparation Example 1, and surface-reconstructed recycled carbon fiber C was obtained.

[0051] The nylon 6 residual adhesive content of the surface-reconstructed recycled carbon fiber C was measured to be 0.6% by mass, the surface oxygen-to-carbon atom ratio was 0.22, and the carbon fiber tensile strength retention rate was 91%.

[0052] Composite materials were prepared according to the formulations shown in Table 1. Examples 1, 2, and 4 used surface-reconstructed recycled carbon fiber A; Example 3 used surface-reconstructed recycled carbon fiber B; and Example 5 used surface-reconstructed recycled carbon fiber C. Comparative Examples 1 and 2 used recycled carbon fibers containing residual adhesive that had not undergone formic acid degumming, oxygen plasma activation, and aminosilane reconstruction treatment. Comparative Examples 3 and 4 used self-made recycled carbon fiber D and recycled carbon fiber E, respectively.

[0053] The preparation processes for each embodiment and comparative example are as follows: S1. PA6, PA6-g-MAH, antioxidant 1098, antioxidant 168, dispersant and carbon black masterbatch are put into a high-speed mixer and mixed at 50°C for 8 minutes to obtain resin premix.

[0054] S2. The resin premix is ​​fed into a co-rotating twin-screw extruder with a length-to-diameter ratio of 40 through the main feed port. After the nylon 6 is plasticized, the recycled carbon fiber is added through the downstream side feed port of the melting zone. The temperatures of each zone are 220℃, 230℃, 235℃, 240℃, 240℃ and 235℃ respectively, the screw speed is 350 r / min, two sets of kneading elements are set downstream of the side feed port, and the vacuum degree of the vacuum exhaust section is -0.08MPa.

[0055] S3. After water cooling, air drying, and pelletizing, the extruded strips are vacuum dried at 90℃ for 4 hours and then injection molded into standard samples. The samples are then placed in an environment of 23±2℃ and 50%±5% relative humidity for 24 hours before performance testing.

[0056] Table 1. Formulations (parts by weight) for each embodiment and comparative example

[0057] Example 1 According to the formulation of Example 1 in Table 1, a composite material was prepared by using surface-reconstructed recycled carbon fiber A (20 parts by weight), PA6 (72 parts by weight), PA6-g-MAH (4 parts by weight), antioxidant 1098 (0.2 parts by weight), antioxidant 168 (0.4 parts by weight), ethylene bis-stearamide (0.3 parts by weight), and carbon black masterbatch (0.5 parts by weight) in accordance with the above process.

[0058] During the melt blending process, the exposed amino groups on the surface of the reconstructed carbon fiber A undergo a ring-opening reaction with the maleic anhydride groups in PA6-g-MAH. At the same time, the nylon 6 segments of PA6-g-MAH are compatiblely entangled with the matrix nylon 6, forming a chemically bonded continuous interface between the carbon fiber body and the nylon 6 matrix.

[0059] Example 2 According to the formulation of Example 2 in Table 1, a composite material was prepared by using surface-reconstructed recycled carbon fiber A (25 parts by weight), PA6 (67 parts by weight), PA6-g-MAH (4 parts by weight), antioxidant 1098 (0.2 parts by weight), antioxidant 168 (0.4 parts by weight), ethylene bis-stearamide (0.3 parts by weight), and carbon black masterbatch (0.5 parts by weight) in accordance with the above process.

[0060] Example 3 According to the formulation of Example 3 in Table 1, surface-reconstructed recycled carbon fiber B (25 parts by weight) was used, and the amount of dispersant was increased to 0.5 parts by weight compared with Example 2. The amounts of other components were the same as in Example 2. The composite material was prepared according to the above process.

[0061] Example 4 According to the formulation of Example 4 in Table 1, surface-reconstructed recycled carbon fiber A (25 parts by weight) was used. Compared with Example 2, the amount of PA6-g-MAH was increased to 6 parts by weight, and the amount of PA6 was adjusted to 65 parts by weight accordingly. The amounts of the remaining components were the same as in Example 2. The composite material was prepared according to the above process.

[0062] Example 5 According to the formulation of Example 5 in Table 1, surface-reconstructed recycled carbon fiber C (25 parts by weight) with a KH550 dry matter loading of 1.5% was used, and the amounts of the remaining components were the same as in Example 2. The composite material was prepared according to the above process.

[0063] Comparative Example 1 According to the formulation of Comparative Example 1 in Table 1, 20 parts by weight of recycled carbon fiber containing residual adhesive that has not undergone formic acid degumming, oxygen plasma activation and aminosilane reconstruction treatment were used to replace the surface reconstructed recycled carbon fiber. The amounts of the remaining components were the same as in Example 1. The composite material was prepared according to the above process.

[0064] Comparative Example 2 According to the formulation of Comparative Example 2 in Table 1, the surface-reconstructed recycled carbon fiber (25 parts by weight) containing residual adhesive was replaced with recycled carbon fiber containing residual adhesive that had not undergone formic acid degumming, oxygen plasma activation and aminosilane reconstruction treatment. The amounts of the remaining components were the same as in Example 2. The composite material was prepared according to the above process.

[0065] Comparative Example 3 One kilogram of recycled carbon fiber containing residual nylon 6 was vacuum dried at 90°C for 3 hours. It was then added to 10 L of 85% formic acid aqueous solution and extracted at 60°C and 50 r / min for 50 minutes. After hot filtration, it was washed sequentially with 2 L of 85% fresh formic acid aqueous solution, 5 L of a mixture of ethanol and water (80:20 volume ratio), and deionized water until the pH of the washing solution reached 6.5 and the conductivity was no higher than 100 μS / cm. The carbon fiber was then vacuum dried at 90°C for 4 hours to obtain recycled carbon fiber D, which had only undergone formic acid desizing. Recycled carbon fiber D was not activated by oxygen plasma or treated with γ-aminopropyltriethoxysilane.

[0066] The residual nylon 6 content of the recycled carbon fiber D was determined to be 0.64% by mass, the surface oxygen-to-carbon atom ratio was 0.10, and the carbon fiber tensile strength retention rate was 95%.

[0067] According to the formulation of Example 2, 65 parts by weight of nylon 6 resin, 30 parts by weight of recycled carbon fiber D, 3 parts by weight of PA6-g-MAH3, 0.1 parts by weight of antioxidant 1098, 0.2 parts by weight of antioxidant 168, 0.2 parts by weight of dispersant, and 1 part by weight of carbon black masterbatch were melt-blended. The resin components were added through the main feed port, and the recycled carbon fiber D was added through the side feed port downstream of the melting zone; the temperatures of each zone were 220°C, 230°C, 235°C, 240°C, 240°C, and 235°C, respectively; the screw speed was 350 r / min; and the vacuum degree was -0.08 MPa. After extrusion, cooling, pelletizing, and drying, the composite material of Comparative Example 3 was obtained.

[0068] Comparative Example 4 Take 1 kg of recycled carbon fiber containing nylon 6 residue and vacuum dry it at 90℃ for 3 hours; place it in a rotary low-temperature plasma treatment device and treat it for 5 minutes under the conditions of oxygen pressure of 40 Pa, treatment power of 160 W and turning speed of 10 r / min. During the treatment, control the temperature of the recycled carbon fiber to not exceed 80℃.

[0069] The plasma-treated carbon fibers containing residual adhesive were added to 10 L of 85% formic acid aqueous solution and extracted at 60 °C and 50 r / min for 50 min. After hot filtration, the fibers were washed sequentially with fresh formic acid aqueous solution, ethanol-water mixture, and deionized water until the pH of the washing solution was 6.5 and the conductivity was not higher than 100 μS / cm. The fibers were then vacuum dried at 90 °C for 4 h.

[0070] To avoid altering the silane treatment variables simultaneously, the same silane treatment as in Preparation Example 1 was performed after formic acid degumming, but without additional plasma activation. Specifically, an ethanol-water treatment solution with a KH550 mass concentration of 1.0% was prepared, with an ethanol-water volume ratio of 80:20. The pH was adjusted to 5.0 using acetic acid, and pre-hydrolyzed for 30 min. The treatment solution was sprayed onto the surface of the recovered carbon fibers after formic acid degumming, with an application rate of 1.0% of the theoretical dry matter loading of the KH550 based on the mass of the recovered carbon fibers. The solution was dried at 80°C for 1.5 h, followed by heat treatment at 115°C for 45 min to obtain the reverse-processed recovered carbon fiber E.

[0071] The residual nylon 6 content of the recycled carbon fiber E was determined to be 0.68% by mass, the surface oxygen-to-carbon atom ratio was 0.12, and the carbon fiber tensile strength retention rate was 94%.

[0072] Comparative Example 4 composite material was prepared using the same formulation and melt blending conditions as Example 2.

[0073] Test The mechanical properties and heat distortion temperature of the composite materials obtained in Examples 1-5 and Comparative Examples 1-4 were tested using the methods described above, and the results are shown in Table 2.

[0074] Table 2. Performance test results of composite materials in each embodiment and comparative example

[0075] As can be seen from Table 2, the amount of recycled carbon fiber used in Example 1 and Comparative Example 1 is similar. The tensile strength, flexural strength, notched impact strength and heat distortion temperature of Example 1 are significantly higher than those of Comparative Example 1. The amount of recycled carbon fiber used in Example 2 and Comparative Example 2 is similar, and they also show the same trend.

[0076] The above comparison shows that the three-step synergistic treatment of residual adhesive removal, reconstruction of oxygen-containing functional groups on the surface, and reactive compatibilization is beneficial to improving the load transfer between recycled carbon fibers and the nylon 6 matrix. This effect cannot be achieved by using untreated recycled carbon fibers containing residual adhesive.

[0077] Example 3, compared to Example 2, increased the amount of dispersant, resulting in a slight improvement in tensile, flexural, and impact properties, indicating that an appropriate amount of dispersant is beneficial in reducing the agglomeration of high-content recycled carbon fibers. Example 4, compared to Example 2, increased the amount of PA6-g-MAH, resulting in improved notched impact strength, but decreased tensile, flexural, and heat distortion properties, indicating that there is a suitable dosage range for reactive compatibilizers. When rigidity, toughness, and heat resistance are required simultaneously, 3 to 5 parts by weight of PA6-g-MAH is preferred.

[0078] Example 5 uses surface-reconstructed recycled carbon fiber C with a KH550 dry matter loading of 1.5%, which has good overall performance, indicating that within the loading range defined by the present invention, increasing the coverage of the effective interface layer can improve the interface bonding; however, the silane dry matter loading should not exceed 1.5% of the mass of the recycled carbon fiber to avoid the formation of an excessively thick self-condensation layer.

[0079] After formic acid degumming, the isolation effect of the aged nylon 6 residue on the surface of the recycled carbon fibers was weakened, and the carbon fiber dispersion and matrix wettability were improved. Therefore, the tensile strength, flexural strength, and heat distortion temperature of Comparative Example 3 were all higher than those of the untreated Comparative Example 2. However, since the carbon fiber surface after degumming contained fewer oxygen functional groups and no aminosilane interface layer was formed, the carbon fiber and PA6-g-MAH were mainly bonded by physical adsorption and limited polar interactions, and the performance was still significantly lower than that of Example 2.

[0080] In Comparative Example 4, oxygen plasma mainly acts on the surface of nylon 6 residual adhesive, and subsequent formic acid removal removes the activated residual adhesive and its surface functional groups. Although KH550 treatment is still performed afterward, the carbon fiber body after adhesive removal lacks sufficient anchoring sites such as hydroxyl and carboxyl groups, and some KH550 exists in the form of self-condensation compounds or physical adsorption. Therefore, its performance is only slightly higher than that of Comparative Example 3, which only underwent formic acid removal.

[0081] Example 2 follows the sequence of "first degumming, then plasma activation, and then silane reconstruction" to allow oxygen plasma to directly act on the exposed recycled carbon fiber body, forming stable oxygen-containing functional groups. KH550 further condenses with the functional groups and reacts with PA6-g-MAH through exposed amino groups, thus forming a continuous reactive interfacial bridging structure and obtaining higher mechanical and heat resistance properties.

[0082] In the case of activation followed by degumming (Comparative Example 4), plasma activation mainly occurs on the surface of the residual adhesive rather than on the carbon fiber body. The oxygen-containing functional groups formed are carried away with the dissolution of the residual adhesive, resulting in insufficient oxygen-containing functional group density on the surface of the carbon fiber body. Consequently, the aminosilane interface layer cannot be stably anchored on the carbon fiber body. Therefore, the processing sequence of degumming, activation, and then constructing the aminosilane interface layer ensures that the interface layer is directly established on the recycled carbon fiber body, which is the key to achieving the superior performance of this invention.

[0083] It is understood that the mass concentration of the formic acid aqueous solution is not limited to 85%, and can effectively dissolve nylon 6 residue in the range of 80% to 90% while causing minimal damage to the carbon fiber itself. The extraction temperature is not limited to 60°C, and can be carried out in the range of 50 to 70°C, preferably 55 to 65°C.

[0084] It is understood that the oxygen-containing gas is not limited to pure oxygen, but can also be an oxygen-argon mixture with an oxygen volume fraction of not less than 60%. The alkoxysilane containing primary amino groups is not limited to γ-aminopropyltriethoxysilane, but can also be other alkoxysilanes containing primary amino groups, as long as a stable silane interface layer with exposed amino groups can be formed on the carbon fiber surface.

[0085] It is understood that the nylon 6 compatibilizer containing anhydride groups is not limited to maleic anhydride-grafted nylon 6, but can also be other graft copolymers containing anhydride groups that can react with amino groups and are compatible with the nylon 6 matrix. Depending on the impact performance requirements, a small amount of maleic anhydride-grafted styrene-ethylene-butene-styrene block copolymer can also be used in combination with maleic anhydride-grafted nylon 6, but its dosage should not be such that the elastomer phase forms a continuous phase.

[0086] Formic acid extract can be recovered by filtration and vacuum distillation; dissolved nylon 6 can be recycled by adding non-solvent for precipitation, washing, and drying to reduce solvent consumption and waste discharge. In continuous production, an atmospheric pressure plasma jet device can be used to process the unfolded recycled carbon fiber bundles, but the processing speed and power should be controlled to ensure that the surface oxygen-to-carbon atom ratio and the retention rate of carbon fiber tensile strength are within the ranges defined in this invention.

[0087] The composite material granules obtained by this invention can be formed by injection molding, extrusion or compression molding, and are suitable for applications such as extruded sheets, mechanical structural parts, electronic and electrical housings and lightweight automotive components.

[0088] In summary, this invention enables the direct establishment of a chemically bonded continuous interface on recycled carbon fiber. The silane interface layer containing exposed amino groups forms a reactive bridge with PA6-g-MAH during the melting process. Simultaneously, the PA6-g-MAH segments are compatible with the nylon 6 matrix, thereby improving the interfacial load transfer capacity and enhancing the mechanical and heat resistance properties of the recycled composite material. Therefore, this invention effectively overcomes the various shortcomings of existing technologies and possesses high industrial applicability.

[0089] The terms used in this specification, such as "upper," "lower," "left," "right," "front," "back," "middle," and "one," are merely for clarity of description and are not intended to limit the scope of the invention. Any changes or adjustments to their relative relationships, without substantially altering the technical content, shall also be considered within the scope of the invention.

[0090] The above embodiments are merely illustrative of the principles and effects of the present invention and are not intended to limit the invention. All equivalent modifications or alterations made by those skilled in the art without departing from the spirit and technical concept disclosed in this invention should still be covered by the claims of this invention.

Claims

1. A recycled carbon fiber reinforced nylon 6 composite material, characterized in that, Including nylon 6 resin, surface-reconstructed recycled carbon fiber, nylon 6 compatibilizer containing anhydride groups, antioxidants, and dispersants; The surface-reconstructed recycled carbon fiber includes a recycled carbon fiber body and a silane interface layer containing exposed amino groups loaded on the surface of the recycled carbon fiber body; the recycled carbon fiber body is derived from waste carbon fiber reinforced nylon 6 material, and its surface residual adhesive content is not higher than 1.5 wt%, and the surface oxygen-carbon atom ratio is 0.15 to 0.25; the dry matter mass of the silane interface layer is 0.5% to 1.5% of the mass of the recycled carbon fiber body.

2. The recycled carbon fiber reinforced nylon 6 composite material according to claim 1, characterized in that, The content of the nylon 6 resin is 65-80 parts, the content of the surface-reconstructed recycled carbon fiber is 15-30 parts by weight, the content of the nylon 6 compatibilizer containing anhydride groups is 3-6 parts by weight, the content of the antioxidant is 0.3-0.8 parts by weight, and the content of the dispersant is 0.2-0.4 parts by weight.

3. The recycled carbon fiber reinforced nylon 6 composite material according to claim 1, characterized in that, The nylon 6 compatibilizer containing anhydride groups is maleic anhydride-grafted nylon 6, with a maleic anhydride grafting rate of 0.6% to 1.2%.

4. The recycled carbon fiber reinforced nylon 6 composite material according to claim 1, characterized in that, The relative viscosity of the nylon 6 resin is 2.3 to 2.7; the antioxidant is composed of hindered phenolic antioxidant and phosphite antioxidant, and the mass ratio of the hindered phenolic antioxidant to the phosphite antioxidant is 1:1 to 1:3; the dispersant is one or two of ethylene bis-stearamide and montanate.

5. A method for preparing surface-reconstructed recycled carbon fibers, characterized in that, Includes the following steps: (1) The recycled carbon fiber containing nylon 6 residue was graded and pre-dried; (2) The pre-dried recycled carbon fiber obtained in step (1) is added to an aqueous formic acid solution with a mass concentration of 80% to 90% and subjected to low-shear extraction at 50 to 70°C to selectively dissolve the nylon 6 residue. After graded displacement washing and vacuum drying, the residue content is reduced to no more than 1.5% by mass. (3) Place the degummed recycled carbon fiber obtained in step (2) into a plasma treatment chamber with a turning mechanism, introduce oxygen-containing gas, and perform low-temperature oxygen plasma activation treatment. Control the carbon fiber temperature to be no higher than 80°C so that the surface oxygen-carbon atom ratio of the obtained recycled carbon fiber body reaches 0.15 to 0.25, and the carbon fiber tensile strength retention rate is no less than 90%. (4) Within 0.5 to 2 hours after the oxygen plasma activation in step (3), the pre-hydrolyzed aminosilane is applied to the surface of the recycled carbon fiber body obtained in step (3), so that the dry matter loading of the aminosilane is 0.5% to 1.5% of the mass of the recycled carbon fiber body. Then, after drying and heat treatment, a silane interface layer containing exposed amino groups is formed to obtain the surface reconstructed recycled carbon fiber.

6. The preparation method according to claim 5, characterized in that, In step (2), the extraction temperature is 55-65℃, the extraction time is 40-60 min, and the liquid-to-solid ratio is 10-12 mL / g; The washing process includes: rinsing with an aqueous formic acid solution of the same concentration as the extract, followed by washing 2-3 times with a mixture of ethanol and water at a volume ratio of 70:30 to 90:10, and finally washing with deionized water until the pH of the washing solution is 6.0-7.0 and the conductivity is not higher than 100 μS / cm; the vacuum drying conditions are 80-100℃, vacuum degree not higher than -0.08 MPa, and drying for 3-6 hours.

7. The preparation method according to claim 5, characterized in that, In step (3), the oxygen-containing gas is oxygen or an oxygen-argon mixture with an oxygen volume fraction of not less than 60%; the plasma activation treatment conditions are: gas pressure 20-80 Pa, power 100-250 W, treatment time 3-8 min, and turning speed 5-20 r / min.

8. The preparation method according to claim 5, characterized in that, In step (4), the aminosilane is selected from alkoxysilanes containing primary amino groups, and the alkoxysilane containing primary amino groups is selected from γ-aminopropyltriethoxysilane.

9. A method for preparing recycled carbon fiber reinforced nylon 6 composite material, characterized in that, Includes the following steps: S1. Nylon 6 resin, nylon 6 compatibilizer containing anhydride groups, antioxidant and dispersant are mixed to obtain resin premix; S2. The resin premix is ​​fed into the co-rotating twin-screw extruder through the main feed port. After the nylon 6 resin has been plasticized, the surface-reconstructed recycled carbon fiber prepared by the preparation method as described in any one of claims 5 to 8 is added through the side feed port downstream of the melt zone. S3. The extrudate obtained in step S2 is cooled, pelletized, and vacuum dried at 80-100°C for 3-6 hours to obtain the recycled carbon fiber reinforced nylon 6 composite material.

10. The preparation method according to claim 9, characterized in that, In step S2, no more than two sets of kneading elements are provided downstream of the side feed port, and a vacuum exhaust section with a vacuum degree of -0.06 to -0.09 MPa is provided. The temperature from the main feed inlet to the machine head is controlled sequentially as follows: 220-230℃, 225-235℃, 230-240℃, 235-245℃, 235-245℃, and 230-240℃.

Citation Information

Patent Citations

  • Waste carbon fiber reinforced nylon 6 composite material and preparation method thereof

    CN102181150A

  • Recovered carbon fiber-reinforced nylon composite material as well as preparation method thereof

    CN103554904A